2021
DOI: 10.3390/rs13102018
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Mature Post-Agricultural Forests in the Polish Eastern Carpathians with Archival Remote Sensing Data

Abstract: Post-WWII displacements in the Polish Carpathians resulted in widespread land abandonment. Most of the pre-war agricultural areas are now covered with secondary forests, which will soon reach the felling age. Mapping their exact cover is crucial to investigate succession–regeneration processes and to determine their role in the landscape, before making management decisions. Our goal was to map post-agricultural forests in the Polish Eastern Carpathians using archival remote sensing data, and to assess their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…As the mission of CORONA was to provide images, especially of the Soviet Union and China [51], these two countries were featured in most LULC studies in which CORONA data were used. Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As the mission of CORONA was to provide images, especially of the Soviet Union and China [51], these two countries were featured in most LULC studies in which CORONA data were used. Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61].…”
Section: Discussionmentioning
confidence: 68%
“…Due to the availability of CORONA imagery since 1995, many researchers used the data to study various environmental processes [23], for instance, past land cover in the Caucasus Mountains [24], forest habitat fragmentation in the Bucegi Mountains, Romania [25], and post-agricultural forest succession in the Carpathian mountains [26]. In many studies, CORONA images were used jointly with other geospatial data to assess changes in land use and land cover (LULC) since the 1960s [27,28], with several studies reporting substantial difficulties when processing the data [6,29,30].…”
Section: Satellite and Camera Time Period Resolutionmentioning
confidence: 99%
“…Using CORONA data to backdate historical topographic maps allowed to extend a study period, providing high accuracy map for analyzing forest pattern and a better understanding of the ALA process and its consequences. As, except for aerial imagery, there is no other high-resolution imagery for the region, CORONA offers the potential of determining the intensity of ALA over the long-term in the entire region due to its accessibility and coverage [55,56]. While this study used time-consuming manual vectorization and geo-referencing of the CORONA images, several studies offer new tools and methods that may accelerate processing of the CORONA data into useful land cover products [31,57].…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1930s, aerial photographs have been systematically collected (Pinto et al, 2019), whereas civilian and commercial satellite images with increasingly higher resolution are available since the 1970s (Belward & Skøien, 2015). Both of these data sources have been extensively used to approach past cultural landscapes in mountainous regions (Jabs‐Sobocińska et al, 2021; Malek et al, 2014; Millican et al, 2017).…”
Section: Introductionmentioning
confidence: 99%